Fluid mechanics of environmental interfaces - Gualtieri, Carlo; Mihailovic, Dragutin T. (CRC Press, 2013)
"The second edition of this successful textbook still focusses on the concept of "environmental interface". An environmental interface is defined as a surface between two abiotic or biotic systems, in relative motion and exchanging mass, heat and momentum through biophysical and/or chemical processes. These processes fluctuate temporally and spatially. The book first treats exchange processes occurring at the interfaces between atmosphere and the surface of the sea, and atmosphere and land surface. These exchanges include the effect of vegetation, transport of dust and dispersion of passive substances within the atmosphere. Processes at the environmental interfaces of freshwater, such as gas-transfer at free-surfaces of rivers, advective diffusion of air bubbles in turbulent water flows and boundary-layers phenomena in vegetated open channels are also described. Finally, the book deals with the phenomena that affect transport of material to and from the surface of an organism, including molecular and turbulent diffusion. The relevant issues related to mass transfer to and from benthic plants and animals are further considered in detail. In this second edition, chapters are updated and five new chapters have been added to make the coverage of the subject area complete. The book will be of interest to graduate students and researchers in environmental sciences, civil engineering and environmental engineering, (geo)physics, atmospheric science, meteorology, limnology, oceanography, and applied mathematics"-- Provided by publisher.
"A Balkema book."
Keywords: Geophysics -- Fluid models.; Fluid mechanics.; Atmospheric turbulance.; Hydrology.; Ocean-atmosphere interaction.; elektronické knihy; electronic books